Acquiring skill in sport: a constraints-led perspective - Davids, K.; Araujo, D.; Shuttleworth, R.; Button, C. (International Journal of Computer Science in Sport, 2003)
Recently, sciences of complexity and chaos have been applied to the study of phenomena in sport with a view to enhancing understanding of approaches to performance, training and coaching (e.g., Mack et al., 2000; MayerKress. 2001). For example, applications of nonlinear dynamics to the study of skilled performance and learning, have modelled athletes as dynamical movement systems (e.g., Davids, et al., 2000; Davids, et al., 2002). Movement coordination and control in sport performers involves two dimensions: (i) coordination between important limb segments over space and time to ensure appropriate temporal sequencing in the movements of joint segments when performing actions such as kicking or running; and (ii) coordination of effectors constrained by important objects, surfaces or events in the environment (Turvey, 1990). These applications are beginning to provide useful insights into processes of motor skill acquisition for players and coaches. The aims of this paper are to: (i) present a theoretical overview of complex, dynamical movement systems which are relevant for the study of coordination processes; (ii) review some of the key constraints on emergent coordination processes; and, (iii) draw some implications for coaching behaviours, such as the use of augmented feedback, from a constraintsled approach.